Synthesis and characterization of the V-doped Li0.3La0.57Ti1-xVxO3 solid electrolyte for all-solid state lithium-ion batteries (2022)
ABSTRACT: All-solid-state Li-ion batteries (ASSB) are one of the future alternatives for electrochemical energy storage, because it exhibits high energy density and safety. The solid electrolyte in the ASSB is a key element to improve the stability and reduce the flammability of lithium batteries [1]–[3]. Solid electrolytes can inhibit dendrites formation in lithium batteries during the charge-discharge processes extending the cycle life. Nevertheless, ASSBs industrial and commercial development have some challenges associated with the lower li-ion conductivity of solid electrolytes (1.0x10–4S/cm) respect to the liquid electrolytes (1.0x10–2S/cm), as well as high interfacial resistance due to the poor contact and interfacial reactions between the solid electrolyte and active materials. Perovskite-type oxides [4] and sulfide-type [5] are promising solid electrolytes for all-solid-state batteries. Although the Li0.34La0.51TiO2.94 perovskite(ABO3) shows high chemical stability, high bulk ionic conductivity (1.0x10–3S/cm), the total ionic conductivity is lower (1.96x10−5S/cm) because of the grain boundary resistance, which reduces the +transport[6]. To reduce the grain-boundary resistance it has been proposed the reduction the activation energy. Doping the B site of the perovskite structure with cations of smaller ionic radius is an alternative to decrease the interatomic bonding forces and improve the lithium conductivity [7]. In this work, we present the synthesis of the Li0.34La0.51Ti1-xVxO3(x=0-0.05) using the sol-gel method followed by a sintering process at high temperature (1200°C) as a potential solid electrolyte for Li-ion batteries. The XRD pattern indicates the formation of Li0.34La0.51Ti1-xVxO3 with perovskite structure in the orthorhombic crystalline system, showing a decrease of the unit cell with the vanadium doping, which can be attributed to the V+5 substitution, which has an ionic radius (0.54Å), lower than Ti+4(0.605Å) in B cation of perovskite structure. The solid electrolyte Li0.34La0.51TiO3 without vanadium exhibits the highest total ionic conductivity 4.54x10-5S/cm, and the Li0.34La0.51Ti0.98V0.02O3 exhibits the best grain conductivity (7.43x10-4S/cm).